Determining the Relationship between Lower Limbs Strength Parameters and Balance in 5-8-Year-Old Children Practicing Dance - D. Chilom; A. Mateescu; C. Mihaiu; C. Moga; M.F. Grigore (Bulletin of the Transilvania University of Braşov: Series IX Sciences of Human Kinetics)
This paper aims to determine the relationship between parameters of lower limb strength and balance in 5-8-year-old children practicing dance. Methods. So, an exploratory study was organized with a group of 24 children aged 5-8 years from the National Palace of Children of Bucharest. Tests used: Test 1 (15 jumps free arms), Test 2 - static balance (SB), Test 3 – lateral dynamic balance (LDB) and Test 4 vertical dynamic balances (VDB). Parameters: performance, front and back inside (LDB), left and right inside (VDB), avg. deviation. In this regard, establishing the relationship degree between lower limb strength parameters and balance in 5-8-year-old dancers depends on the number of negative correlations, especially between average deviation parameters.